THE PRICE-LEVEL STUDY OF THE AMERICAN ACCOUNTING ASSOCIATION. - Mason, Perry (The Accounting Review, 1955)
Abstract This article presents the price-level study of the American Accounting Association. The rate of return on the total investment is probably the most important single calculation which can be made from financial statements. The second set of percentages shows the rates of return for 1941, for 1951, and the average for the period 1941-1951. In general, the rate of return on the total investment on a constant-dollar basis was about half of the reported rate. One of the common complaints about income taxes is that they make no allowance for the changing value of the dollar. They tax reported income without taking into account that the amount needed to maintain capital in terms of its purchasing power has substantially increased. Also, firms having a relatively large investment in depreciable assets are discriminated against as compared with other industries whose costs are much dozer to current figures. It is important to note, however, that neither the company as a business entity nor the common stock interest was worse off than if the issuance of the preferred stock had been postponed until the very day on which the funds were needed.